2002
DOI: 10.1007/bf02897975
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhances tumorigenicity induced by N-ethyl-N′-nitro-N-nitrosoguanidine in the duodenum of mice

Abstract: Quercetin, a flavonoid, widely distributed in many fruits and vegetables, is well known to have an antitumor effect despite its mutagenicity. In this study, we examined the effect of dietary quercetin on duodenum-tumorigenicity of mice induced by a chemical carcinogen, N-ethyl-N'-nitro-N-nitrosoguanidine (ENNG). Eight-week-old male C57BL/6 mice were divided into 4 groups; ENNG without quercetin (group A), ENNG with 0.2% quercetin (group B), ENNG with 2% quercetin (group C), and 2% quercetin without ENNG (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Most studies revealed no or even chemo‐preventive effects of quercetin (details see). However, a few studies using different carcinogens (N‐ethyl‐N’‐nitro‐N‐nitrosoguanidin, azoxymethane, nitrosomethylurea or 17β‐estradiol) reported also an enhanced tumor development in duodenum, colon, pancreas, kidney or mammary glands of rodents after quercetin treatment with 0.2 to 3.4 % in feed (corresponding to approximately 150 to 3400 mg per kg bw and day). Two of these studies started the quercetin treatment in pregnant rats continuing in their offspring and investigated the tumorigenesis in the offspring .…”
Section: Safety Aspectsmentioning
confidence: 99%
“…Most studies revealed no or even chemo‐preventive effects of quercetin (details see). However, a few studies using different carcinogens (N‐ethyl‐N’‐nitro‐N‐nitrosoguanidin, azoxymethane, nitrosomethylurea or 17β‐estradiol) reported also an enhanced tumor development in duodenum, colon, pancreas, kidney or mammary glands of rodents after quercetin treatment with 0.2 to 3.4 % in feed (corresponding to approximately 150 to 3400 mg per kg bw and day). Two of these studies started the quercetin treatment in pregnant rats continuing in their offspring and investigated the tumorigenesis in the offspring .…”
Section: Safety Aspectsmentioning
confidence: 99%
“…The pro-oxidant nature of curcumin would increase cellular ROS levels at higher doses, potentially contributing to carcinogenesis ( López-Lázaro, 2008 ). Furthermore, excessive quercetin intake exacerbates tumorigenicity induced by a chemical carcinogen N-ethyl-N′-nitro-N-nitrosoguanidine (ENNG), in the duodenum of mice ( Matsukawa et al, 2002 ). While the immense health-promoting benefits of epigallocatechin-3-gallate, a study demonstrated that high dose administration of EGCG in mice resulted in hepatotoxicity correlated with inhibition of antioxidant enzymes and Nrf2 targeted genes ( Wang et al, 2015 ).…”
Section: Toxic Effects Of Phytocompoundsmentioning
confidence: 99%